Ichthiophthirius multifiliis responsible for carps death - ΦΩΤΗΣ, ΓΕΩΡΓΙΟΣ (Journal of the Hellenic Veterinary Medical Society, 2019)
I his paper refers to sporadic deaths of young Cyprinus caprio, which had been (ceded in primitivc installations located near Strimonas river. These deaths arc due to ectoparasite i. multililus, which was found at the gills of young Carps.